Analysis of the Development of Thai Reading Index - Kaemkate, Wannee (Journal of Research Methodology, 2023)
Thailand has been changed considerably in various aspects in the past 10 years. Therefore, a reading index should be available to reflect the reading situation of Thai people. This research aimed to create a Thai reading index for reporting the reading situation of Thai people in 2020, and to analyze the development of Thai people’s reading index in relation to reading behavior, reading ability, and reading outcomes by comparing to the baseline data of Thai reading index in 2010. Data were collected using a questionnaire responded by the sample consisting of Thai people from 4 regions, aged 18 years and above, in 2020. The sample of total 4,551 persons was selected by a multistage sampling method as used in the 2010 research to obtain matched pairs in statistics. Data were analyzed using descriptive statistics, confirmatory factor analysis, repeated measures MANOVA, and repeated measures ANOVA. The results can be concluded as follow: The analysis results for creating a Thai reading index for reporting Thai people’s reading situation in 2020 found that the measurement model of Thai reading index fit the empirical data. Factor loadings of all observed variables and factor loadings of reading behavior, reading ability, and reading outcomes were statistically significant at the .05 level. The component with the greatest loading for indicating Thai reading index was reading outcomes, followed by reading ability while reading behavior had the lowest loading. The analysis results can be used to create a Thai reading index for reporting Thai people’s reading situation in 2020. It was found that Thai people had the highest mean in the reading outcomes index (M = 69.84, SD = 17.97), followed by the mean of reading ability index (M = 66.34, SD = 18.87) while the mean of reading behavior index was the lowest (M = 28.48, SD = 14.20). The mean of reading behavior index was lower than 50 while the mean of reading ability index and the mean of reading outcomes index including the overall reading index (M = 59.33, SD = 15.66) were higher than 50. Analysis results of the development of Thai reading index in terms of reading behavior, reading ability, and reading outcomes including the index of overall reading of Thai people compared to the 2010 baseline data found Thai reading index based on the 3 aspects and the index of overall reading decreased from the 2010 baseline data with the statistical significance level of .05.